PERSONALIZING POTENTIALS OF WEBLOG IN EFL CLASSROOMS - Yustinus Calvin Gai Mali (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
A weblog (also called a blog) has been pervasively used as an alternative language learning technology in English as a Foreign Language (EFL) settings. However, there are still limited attempts to shed more lights on the (a) integration of various applications in the blog and (b) how they can be maximized for teaching and learning purposes in the context of Indonesian higher education. Therefore, this study aims to explore issues concerning the use of a tutor blog run in an English Education Study Program of a private university. The exploration focuses on the potentials of the tutor blog and their relevance to current blogging activities as well as draws on related literature and reflective experiences in utilizing the blog in EFL classrooms. This study seems to confirm the potentials of the tutor blog, as asserted by Campbell (2003). The analysis also reveals some possibilities of integrating the blog into other technological applications, which should be beneficial for pre-service and in-service EFL teachers who wish to utilize blogs to support their pedagogical agendas. The study concludes with directions for further studies.